Observer variability in the histopathological reporting of abnormal rectal biopsy specimens. Issue 1 (January 1994) - Lessells, A M; Beck, J S; Burnett, R A; Howatson, S R; Lee, F D; McLaren, K M; Moss, S M; Robertson, A J; Simpson, J G; Smith, G D
Abstract : AIMS–To study the consistency of reporting of abnormal rectal biopsy specimens, especially in the differentiation of inflammatory bowel disease from other causes of abnormality. METHODS–Sixty rectal biopsy specimens were identified from patients presenting with bloody diarrhoea. These were then circulated to the 11 consultant pathologists in the study who filled in a proforma with a list of 12 diagnostic categories and 22 features. RESULTS–Forty one of the 60 cases were examples of inflammatory bowel disease. In 33 of these cases nine or more pathologists had made the diagnosis. Further categorisation into ulcerative colitis and Crohn's disease showed better recognition of ulcerative colitis. In the 19 cases of non-inflammatory bowel disease recognition of pseudomembranous colitis and solitary rectal ulcer syndrome was good, but the results were poorer in the case of infective colitis. CONCLUSION–The findings suggest that a group of consultant pathologists can differentiate between inflammatory bowel disease and other causes of an abnormal rectal biopsy specimen and can also recognise pseudomembranous colitis and solitary rectal ulcer syndrome satisfactorily.